Socio-economic perspective of informal vendors in Chapinero: Bogotá, Colombia - Rincón Báez, William Umar; Soler Hurtado, Andrea Johanna (Cooperativismo & Desarrollo, 2016)
Introduction: Informal sales in Bogota have increased due to the serious unemployment situation the country is going through. Methodology: This research is descriptive and sought to socio-demographically characterize the sample and determine the economic factors of the business and the financial products used by street vendors in the locality of Chapinero in Bogota, Colombia. As a technique, simple random sampling was used with a survey endorsed by three judges. Results: It was found that policies have been inefficient, thus creating different problems. Conclusions: Unemployment, as well as lack of resources and access to loans as seed capital, give rise to factors that, linked to the social problem, find in informal work a form of subsistence. Generally, the same problem is detected in Bogota, especially in Chapinero for being a financial and commercial sector, which provides favorable conditions to promote and multiply informal work. It is shown how informal vendor relocation policies implemented by different district administrations have been unfruitful.
Keywords: public space; informal work; informal loans; relocation programs; street sales.